2014
DOI: 10.1093/cid/ciu150
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intermittent Preventive Treatment With Dihydroartemisinin-Piperaquine on Malaria in Ugandan Schoolchildren: A Randomized, Placebo-Controlled Trial

Abstract: Dihydroartemisinin-piperaquine administered at monthly intervals, but not that dosed once a school term, is a remarkably effective measure for the prevention of incidence of malaria, prevalence of parasitemia, and prevalence of anemia in schoolchildren living in a high-transmission setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
111
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 29 publications
9
111
2
Order By: Relevance
“…The duration of protection was similar with both regimens, with a high level of protection for about 4 weeks followed by a rapid decrease, highlighting the importance of strict timing in SMC programs to ensure that children receive treatment at monthly intervals. These results are consistent with those of previous studies in children (8,9) and a study in adults in Thailand (11), which showed that DHAPQ was well tolerated and highly effective when used for monthly prophylaxis, and with a study in schoolchildren in Uganda, which showed that monthly DHPAQ was well tolerated and reduced malaria incidence by 96% and the prevalence of anemia by 40% (23). In another study in Uganda in younger children, the efficacy of monthly DHAPQ was only 58%, possibly due to poor adherence and underdosing (24).…”
Section: Discussionsupporting
confidence: 92%
“…The duration of protection was similar with both regimens, with a high level of protection for about 4 weeks followed by a rapid decrease, highlighting the importance of strict timing in SMC programs to ensure that children receive treatment at monthly intervals. These results are consistent with those of previous studies in children (8,9) and a study in adults in Thailand (11), which showed that DHAPQ was well tolerated and highly effective when used for monthly prophylaxis, and with a study in schoolchildren in Uganda, which showed that monthly DHPAQ was well tolerated and reduced malaria incidence by 96% and the prevalence of anemia by 40% (23). In another study in Uganda in younger children, the efficacy of monthly DHAPQ was only 58%, possibly due to poor adherence and underdosing (24).…”
Section: Discussionsupporting
confidence: 92%
“…Study samples were from a randomized, double-blinded, placebo-controlled trial conducted in Tororo, Uganda, from 2011 to 2012 (6,39). In brief, 740 schoolchildren aged 6 to 14 years from one primary school in Mulanda subcounty, Tororo District, were enrolled and randomized 1:1:1 to one of three study arms: DP monthly, DP once per school term (four treatments over 12 months), or placebo.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to IPTp with SP, IPTp with DP was associated with lower risks of P. falciparum infection and symptomatic malaria during pregnancy in Kenya (14) and Uganda (15). In Ugandan schoolchildren, monthly IPT with DP was associated with a reduced incidence of malaria and reduced prevalence of parasitemia and anemia compared to DP given approximately once every 3 months or placebo (6,16). Similar results were observed in Ugandan infants when monthly IPT with DP was compared with daily trimethoprim-sulfamethoxazole or monthly SP (7).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In Senegalese children, the incidences of malaria were the same with monthly DP and monthly AQ/SP, although protective efficacies could not be measured due to the lack of a control group (13). In Uganda, monthly DP administered without directly observed therapy to children 6 to 24 months of age had a protective efficacy against malaria of 58%, significantly greater than that of monthly SP or daily trimethoprim-sulfamethoxazole (14), and monthly DP administered to school children 6 to 14 years of age for 1 year had a protective efficacy of 96% (15). In Burkina Faso, intermittent preventive therapy with DP in children aged 3 to 59 months showed 77% protective efficacy compared to 83% for AQ/SP (I. Zongo, unpublished data).…”
mentioning
confidence: 99%